Human Leucocyte Antigen Class II Risk and Protective Alleles in Women with Cervical Intraepithelial Neoplasia - Plisko, Olga; Žodžika, Jana; Jermakova, Irina; Liepniece-Karele, Inta; Eglīte, Jeļena; Rezeberga, Dace (Acta medica Lituanica, 2024)
Background: Persistent human papillomavirus (HPV) infection is a necessary cause for development of cervical precancerous lesions and cervical cancer, however, only a small percentage of women progress to cervical cancer. The local immune response, determined, among other factors, by Human Leucocyte Antigen (HLA) genes, is thought to be significant. Still the results of genome studies are inconsistent and differ between ethnical populations.  The aim of the study was to assess an association between HLA-DQA1*; DQB1*; DRB1* allele’s genetic variants between women with cervical precancerous lesions and healthy controls in Latvia.Materials and methods: From January until April 2017 we enrolled 84 consecutive patients referred for colposcopy to Riga East University Hospital (Latvia) due to abnormal cervical cytology results. 57 women who came for a regular check-up and had normal cytology smears were included in the control group. Material from the cervix was taken for subsequent HLA genotyping of 13 DRB1*, 8 DQA1*, and 12 DQB1* alleles. Colposcopy was performed on all participants. In case of visual suspicion for CIN cervical biopsy was done.Results: There were 57 “no CIN” patients, 23 histologically proven CIN 1 and 61 CIN2+ cases in the study population. CIN2+ was more often associated with DQA1*0401 (OR 6.68, 95% CI 1.47-30.29, p=0.014), DRB*15 (OR 2.99, 95% CI 1.22-7.39, p=0.017), DQB1*0401 (OR 2.91, 95%CI 1.11-7.68, p=0.03), DQA1*0103 (OR 2.72, 95% CI 1.02-7.21, p=0.045), DRB1*11 (OR 2.42, 95% CI 1.10-5.33, p=0.029) and DQB1*0301 (OR 1.94, 95% CI 1.12-3.38, p=0.018). Women with “no CIN” more often had DQB1*0501 (OR 0.17, 95% CI 0.04-0.81, p=0.026), DRB1*16 (OR 0.21, 95% CI 0.06-0.78, p=0.019), DQA1*0301 (OR 0.35, 95% CI 0.14-0.87, p=0.024) and DRB1*14 (OR 0.59, 95% CI 0.01-0.46, p=0.007).Conclusions: In the current study we have demonstrated a strong association with risk and protective HLA class II alleles that are determined by the HLA-DRB1*; DQA1*; DQB1*.
Keywords: cervical intraepithelial neoplasia; human leucocyte antigen; HLA; high-grade cervical lesions